Lung findings on high resolution CT in early ankylosing spondylitis - Kiris, A; Ozgocmen, S; Kocakoc, E; Ardicoglu, O; Ogur, E (Elsevier Sci Ireland Ltd, 2003)
Objective: Ankylosing spondylitis (AS) is a chronic inflammatory disease mainly affecting the axial skeleton and pulmonary involvement is a well known feature of the disease. The aim of this study was to investigate the pulmonary high resolution computed tomography (HRCT) findings of patients with early AS. The relationship between pulmonary function tests (PFT) and HRCT findings was also determined. Subjects and methods: Twenty-eight patients with AS (mean age 30.8 +/- 7.4 and disease duration 7.0 +/- 2.6) were included in the study. Patients with a disease duration of > 10 years or had other pulmonary diseases were excluded. All patients underwent plain chest radiography (posteroanterior and lateral views), thoracic HRCT and PFT. Results: All chest radiographs were normal and HRCT revealed abnormalities in 18 patients. The most common abnormalities seen on HRCT were mosaic pattern (ten of 28), subpleural nodule (seven of 28) and parenchymal bands (five of 28). Seven of ten patients with mosaic pattern revealed air trapping areas on end expiratory scans. Twelve patients had abnormal PFT and all had restrictive type of involvement. Ten of these 12 patients had abnormal HRCT and the remaining two patients had normal HRCT. On the other hand, eight patients with normal PFT had abnormalities on HRCT. Conclusion: Patients with early AS frequently have abnormalities on HRCT, even though they have normal PFT and chest X-ray. Small airway involvement was found as frequent as interstitial lung disease in early AS. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: ankylosing spondylitis; high-resolution CT; interstitial lung disease; air trapping; small airway disease; mosaic pattern